HSP70 Induction by ING Proteins Sensitizes Cells to Tumor Necrosis Factor Alpha Receptor-Mediated Apoptosis - Feng, Xiaolan (American Society for Microbiology, 2006)
ING proteins affect apoptosis, growth, and DNA repair by transducing stress signals such as DNA damage, binding histones, and subsequently regulating chromatin structure and p53 activity. p53 target genes, including the p21 cyclin-dependent kinase inhibitor and Bax, an inducer of apoptosis, are regulated by ING proteins. To identify additional targets downstream of p33(ING1) and p32(ING2), cDNA microarrays were performed on phenotypically normal human primary fibroblasts. The 0.36% of genes affected by ING proteins in primary fibroblasts were distinct from targets seen in established cells and included the HSP70 heat shock gene, whose promoter was specifically induced >10-fold. ING1-induced expression of HSP70 shifted cells from survival to a death pathway in response to tumor necrosis factor alpha (TNF-α), and p33(ING1b) protein showed synergy with TNF-α in inducing apoptosis, which correlated with reduced NF-κB-dependent transcription. These findings are consistent with previous reports that HSP70 promotes TNF-α-mediated apoptosis by binding I-κΒ kinase gamma and impairing NF-κB survival signaling. Induction of HSP70 required the amino terminus of ING1b but not the plant homeodomain region that was recently identified as a histone binding domain. Regulation of HSP70 gene expression by the ING tumor suppressors provides a novel link between the INGs and the stress-regulated NF-κB survival pathway important in hypoxia and angiogenesis.